2008
DOI: 10.2106/jbjs.g.01133
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of Combined Popliteal and Ankle Blocks in Forefoot Surgery

Abstract: A popliteal block in conjunction with an ankle block provides significantly better pain relief than does an ankle block alone in patients undergoing forefoot surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0
7

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 8 publications
1
16
0
7
Order By: Relevance
“…Studies in the literature report that ankle block is effective in early postoperative pain control, allows early mobilization, and prevents adverse effects secondary to oral analgesic use [10-14]. In their prospective study of 71 cases, Russell et al [2] reported that ankle block markedly decreased the postoperative 24-h VAS score and that it is a safe method.…”
Section: Discussionmentioning
confidence: 99%
“…Studies in the literature report that ankle block is effective in early postoperative pain control, allows early mobilization, and prevents adverse effects secondary to oral analgesic use [10-14]. In their prospective study of 71 cases, Russell et al [2] reported that ankle block markedly decreased the postoperative 24-h VAS score and that it is a safe method.…”
Section: Discussionmentioning
confidence: 99%
“…До недоліків проксимальних блокад можна віднести можливість розвитку специфічних ускладнень (пошкодження тазових органів, інфекція), а також тривалий період порушення руху кінцівкою при проксимальних блокадах сідничного і стегнового нервів, що обмежує застосування цієї методики в амбулаторній травматології та відділеннях хірургії "одного дня", відносно велика протяжність симпатичного блоку [29,44,53].…”
Section: блокада сідничного нерва в поєднанні з блокадою стегнового нunclassified
“…При проведенні регіонарної анестезії на стопі і надп'ятково-гомілковому суглобі ряд авторів рекомендують як доповнення до основного блоку в підколінній ямці -блокаду підшкірного нерва стопи для анестезії в ділянці тилу стопи і великого пальця, а також блокаду литкового нерва, що іннервує латеральний край стопи і шкіру мізинця [23,29,53].…”
Section: Ankleblockunclassified
“…53 A recent PRCT (Level I evidence) 59 compared combined ankle and popliteal nerve blockade with ankle block alone for forefoot surgery. In general, toe procedures can be performed under a digital block and forefoot procedures under an ankle block.…”
Section: Which Block?mentioning
confidence: 99%